Analisis Zat Berbahaya Pada Makanan Menggunakan Sari Buah Naga Dan Sari Kunyit - Sindi Try Yuliani; Fira Ardila (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the presence of hazardous substances in food by utilizing the potential of dragon fruit extract and turmeric extract as natural indicators. The proposed method involves testing food samples for color changes induced by these natural extracts, indicating the presence of borax, formaldehyde, or certain synthetic dyes. Dragon fruit extract is expected to show specific color changes in response to certain substances, as is turmeric extract. This innovative approach aims to provide a fast, cost-effective, and environmentally friendly early detection method, particularly for food screening at the household or market level, supporting broader food safety efforts.